2009
DOI: 10.1007/s10546-009-9387-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Emission Determination Using an Inverse-Dispersion Technique

Abstract: Inverse-dispersion calculations can be used to infer atmospheric emission rates through a combination of downwind gas concentrations and dispersion model predictions. With multiple concentration sensors downwind of a compound source (whose component positions are known) it is possible to calculate the component emissions. With this in mind, a field experiment was conducted to examine the feasibility of such multi-source inferences, using four synthetic area sources and eight concentration sensors arranged in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 15 publications
(18 reference statements)
1
52
0
Order By: Relevance
“…Just as with the calculations using data pairs, there was no evidence that ill-conditioning was a problem in this study. Even with very large κ values approaching 200 in this dataset, there were no large errors in emission rate calculations as documented by Flesch et al [17].…”
Section: Two Emission Sourcessupporting
confidence: 66%
See 4 more Smart Citations
“…Just as with the calculations using data pairs, there was no evidence that ill-conditioning was a problem in this study. Even with very large κ values approaching 200 in this dataset, there were no large errors in emission rate calculations as documented by Flesch et al [17].…”
Section: Two Emission Sourcessupporting
confidence: 66%
“…In our calculations with the PIC pairs, κ ranged from 1.5 to 150. While Flesch et al [17] concluded that accurate emission inferences required κ below approximately 20, in this study two emission rates were calculated to within 35% of their correct value even with κ greater than 100.…”
Section: Two Emission Sourcesmentioning
confidence: 59%
See 3 more Smart Citations